Associação do peeling de ácido tricloroacético com fotobiomodulação no tratamento do fotoenvelhecimento cutâneo das mãos: um ensaio clínico controlado, randomizado e duplo-cego - Momolli, Marcos (2022)
Photodamage is a growing concern in contemporary society as it promotes premature skin aging and different pathologies resulting from prolonged and repeated exposure to solar ultraviolet radiation, which is considered the main extrinsic factor of this process. Affected by radiation, the hands represent an important role in the manifestation and visibility of aging, as they are very exposed body regions. The purpose of the study is developed by the potential mechanism of tissue repair, skin rejuvenation, anti-inflammatory and analgesic effects of photobiomodulation, complementing the benefits of chemical exfoliation. This randomized, controlled, double-blind clinical trial aimed to compare the photorejuvenating effects of 20% trichloroacetic acid (TCA) peeling applied alone and the effects of associating 20% ATA peeling with red LED photobiomodulation (PBM) on the treatment of the back of the hands (660 nm; 100 mW; 5 J/cm²). 44 participants were divided into 2 groups and received different therapies according to the allocation group. The experimental group was submitted to 03 sessions of 20% TCA and PBM peeling. The control group also received 03 sessions of 20% TCA peeling associated with simulated PBM. The application sessions took place monthly and the evaluation appointments every fortnight. Analyzes of characteristics related to photoaging such as fine and deep wrinkles, dyschromia and global assessment of the back of the hands were performed using periodic standardized photographs and analyzed by two independent plastic surgeons. A visual-analog pain scale and a 5-point Likert scale were also applied to assess participant satisfaction. For a statistical significance level of 5%, the experimental group showed an improvement in fine wrinkles, deep wrinkles and pain levels after the third treatment session, as well as an improvement in dyschromias and global assessment after the second session compared to the control group. Both groups showed a high degree of satisfaction. Therefore, it can be inferred a beneficial association of PBM in an adjuvant way with 20% TCA in the treatment of photoaging of the hands.